2021
DOI: 10.1073/pnas.2022653118
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress destabilizes symbiotic nutrient cycling in corals

Abstract: Recurrent mass bleaching events are pushing coral reefs worldwide to the brink of ecological collapse. While the symptoms and consequences of this breakdown of the coral–algal symbiosis have been extensively characterized, our understanding of the underlying causes remains incomplete. Here, we investigated the nutrient fluxes and the physiological as well as molecular responses of the widespread coral Stylophora pistillata to heat stress prior to the onset of bleaching to identify processes involved in the bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
174
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(246 citation statements)
references
References 96 publications
(153 reference statements)
14
174
0
Order By: Relevance
“…Globally, we detected in our scRNA-seq dataset a similar number of genes (31,425) to those seen in S . pistillata bulk RNA-seq studies (30,821) ( Liew et al, 2018 ; Rädecker et al, 2021 ; Figure S1K ), and the aggregated scRNA-seq gene expression levels correlated well with levels measured bulk RNA-seq analyses (Rs = 0.803) ( Figure S1L ).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Globally, we detected in our scRNA-seq dataset a similar number of genes (31,425) to those seen in S . pistillata bulk RNA-seq studies (30,821) ( Liew et al, 2018 ; Rädecker et al, 2021 ; Figure S1K ), and the aggregated scRNA-seq gene expression levels correlated well with levels measured bulk RNA-seq analyses (Rs = 0.803) ( Figure S1L ).…”
Section: Resultssupporting
confidence: 55%
“…For comparison of single-cell RNA-seq versus bulk RNA-seq data, we re-mapped reads from two studies ( Liew et al, 2018 ; Rädecker et al, 2021 ) using the same STAR parameters used to map scRNA-seq reads and we used STAR gene count estimates with the same gene intervals defined for our scRNA-seq analysis for compatibility in the comparison.…”
Section: Star Methodsmentioning
confidence: 99%
“…Understanding the diversity of coral heat stress responses both within and between species is critical for predicting future coral performance in a changing ocean. While coral bleaching is a dramatic and easily observable heat stress response (Bollati et al, 2020; Putnam et al, 2017), elevated temperatures can also trigger less visible stress responses in the animal host, even if the symbiosis remains intact (Rädecker et al, 2021). All animals have a range of temperatures to which they are adapted, and once exposed to temperatures beyond this optimal range, can activate a suite of heat stress responses and divert energetic investment toward maintenance processes like homeostasis, at the expense of other more immediately expendable processes such as growth and reproduction (Pörtner, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the physiology of the algal symbionts may modulate the phenotype of their marine invertebrate hosts (Cunning et al, 2015;Howells et al, 2020;Rädecker et al, 2015;Rädecker et al, 2021;Silverstein et al, 2015;Terraneo et al, 2019). As an example, many Durusdinium taxa appear to be relatively stress-tolerant (LaJeunesse et al, 2014), for example, to warm and cold temperature-induced bleaching (Silverstein et al, 2017), and certain specialist Cladocopium taxa are found in the hottest coral-containing waters on Earth (Hume et al, 2016).…”
Section: Introductionmentioning
confidence: 99%